RNA-seq and nuclear proteomics provide insights into the lactation regulation mechanism of goat transfected IGF-I and GH recombinant vectors. (October 2021) - Fu, Shaodong; Shen, Xuehuai; Wang, Xudong; Zhou, Yilin; Zhang, Jinqiu; Miao, Jinfeng
Abstract: There exists little available information on the mechanisms of lactation regulation until now. In order to explore the underlying mechanism, we injected IGF-I and GH recombinant vectors into the mammary gland, then RNA-seq analysis and nuclear proteomics were used for rapid high-throughput screening of DEGs and DEPs in the two groups linked to lactation regulation. KEGG analysis of 206 DEGs showed that the same 4 of top 10 enrichment pathways (ECM receptor interaction, protein digestion and absorption, focal adhesion and phagosome) involved in 4 co-expressed genes (IDO, BTG1, ITGB6 and keratin 83), the two groups enriched different metabolic pathways yet. Nuclear proteomics analysis showed 75 and 36 DEPs in the IGF-I and GH group respectively; Sixteen common proteins were identified between the IGF-I group and GH group, four of which (ALB, TPT1, CXXC-5 and ACTR2) significantly decreased and three of which (PRP1, PAG-9 and Hsp70) significantly increased. Similarly, DEPs in the two groups were enriched in same one of top 10 enrichment pathways (PI3K-Akt signaling pathway). Protein-protein interaction networks highlighted the contribution of glycosphingolipid biosynthesis, porphyrin and chlorophyll metabolism and the Jak-STAT signaling pathway to lactation regulation of GH and IGFI. GH and IGF-I improve milk yield, which may be linked to important nodal proteins (ALB and ACTB). Our research advances the understanding of the mammary gland transcriptome and nuclear proteomics during GH and IGF-I overexpression. Individual genes, proteins and pathways in this study point towards potential targets for lactation regulation. Highlights: pIN and pcGH-20 plasmid improved lactation via different metabolic pathways. pIN plasmid affected purine, pyrimidine, amino acid and glycerophospholipid metabolism. pcGH-20 plasmid affected sphingolipid, glycerolipid and retinol metabolism and citrate cycle.